PENENTUAN AKTIVITAS INULINASE PADA SUBSTRAT INULIN A1-KG DARI BAKTERI MESOFILIK RIZOSFER UMBI DAHLIA (DAHLIA SP) - Awaluddini Ma’riffattullah, Minda Azha ,Iryani (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Inulinase is an enzyme that can catalyze inulin hydrolysis reaction to fructose andfructooligosaccharide (FOS) which two important compounds in the food industry. Thisstudy aims to determine the optimum activity of inulinase on variations in pH (3.5; 4; 4.5;5; and 5.5), temperature (18ºC; 25ºC; 28ºC; 37ºC and 45ºC); and substrate concentration(0.5%; 1%, 1.5%, 2% and 2.25%) with an incubation time of 30 minutes. In addition, thisstudy also aims to determine the value of KM, Vmax and determine the type of action ofinulinase. Determination of the optimum activity of inulinase was determined by DNSreagents whose absorbance was measured using spice at λ 536 nm. Determination of thetype of action of the inulinase enzyme is determined by the TLC method. Inulinase activityfound optimum at pH 4; 40ºC temperature and 2% substrate concentration. The values ofKM and Vmax inulinase are 3.12% (w / v) and Vmax is 0.288 U / mL. The type of action ofinulinase enzymes found in Rhizosphere bacteria dahlia isolates A1-KG is endoinulinase.Keywords: inulin, inulinase, inulinase enzyme activity, and type of inulinase action frombacteria.